NATURAL SURROUNDINGS OF MEDIEVAL SOCIETIES IN THE UPPER KAMA VALLEY - Kopytov, S.V.; Demakov, D.A. (Perm Federal Research Centre Journal, 2017)
There are some 25 archaeological sites of the Middle Age located along the banks of the upper River Kama in the area from Bondyug settlement to the mouth of the River Vishera. Complex paleogeographic research works have been carried out on this segment of the river valley. These research works were based on geomorphological and geochronological methods, as well as paleochannel studies. A mapping of uneven-aged floodplain generations was performed. The research of the sections of the upper River Kama’s floodplain generations helped to establish the age of the floodplain geosystems (the time of occurrence of their invariant beginning) according to the location features of soils, peat, floodplain, oxbow and channel alluviums. The age of geosystems may change depending on their modern location in the river valley (their remoteness from the channel) and the kind of floodplain zone they belong to in the formation period. The range of these values can be quite big (hundreds - thousands of years). The research has shown that there is some dependence between the age of the archaeological sites and their location in the valley. Ancient settlements and burial grounds were mainly located on the root bank of the river, however, village settlements - on the edge of the ledge of the second floodplain generation. The age of this generation is about 1,5 thousand years. The channel at the formation period of this floodplain surface had in general its current configuration. It has been established that the operation period of the modern floodplain geosystem is no more than 400 years.